STRATEGI PEMBELAJARAN NGAJI AL-QUR'AN MENGGUNAKAN METODE IQRA’ DESA BUDDAGAN PAMEKASAN - Sri Rizqi Wahyuningrum; Fatima Shalha Nashriya; Nur Aulia Sury; Rif’atus Sa’adah; Bagus Tricahya Priyatna; Akhmad Suyitno (Collaborative: Jurnal Pengabdian Masyarakat, 2026)
Education, religious life, and environmental cleanliness are three important components in improving the quality of life of the community, especially in rural areas. In Buddagan Village, these three components still require continuous attention and assistance so that the community can develop holistically. The purpose of this study is to help the community of Buddagan Village by providing education, religious life, and environmental cleanliness. The research method used was Participatory Action Research (PAR), implementing a forty-two-day Community Service program, which included lessons at school, parenting seminars, and a Quran recitation program. The results showed that the program successfully increased community awareness of religion, education, and child care. Teaching at schools and prayer rooms improved the quality of children's education, and the parenting seminars successfully increased parental awareness. Children's ability to read the Quran was improved through the Quran recitation program. The program was successful thanks to active community participation and parental support. The Iqra' method is widely used to accelerate the ability to read the Quran, especially for early childhood. Participation in community service strengthens Quranic learning activities through the support of additional teaching staff, structured schedule management, and creative approaches that increase children's motivation to continue learning to read the Quran fluently and sustainably.